Management of the Deep Learning Approach to Developing the Character of Elementary School Students - Emilya Nurihayati; Hanafiah (Green Publisher Indonesia, 2026)
This study aims to describe and analyze the management of deep learning approach to develop the character of elementary school students. The focus of this study is on the plan, do, check and act of learning that integrates deep learning with meaningful projects as the main strategy. The study was conducted qualitatively with a case study approach in two public elementary schools in Cianjur Regency, namely SDN Sayang 4 Cianjur Subdistrict and SDN Cinawala Cikalongkulon Subdistrict. Data collection was carried out through observation, in-depth interviews, and documentation study. The results of the study indicate that learning management with a deep learning approach can increase active student participation, encourage reflective thinking, and strengthen character values such as responsibility, mutual cooperation, and integrity. The main supporting factors for successful implementation are the leadership of the principal, teacher collaboration, and parental involvement. The challenges faced include limited time, resources, and teacher readiness in designing projects that are appropriate to the local context. The conclusion of this study is that the application of learning management with a deep learning approach can be an effective strategy in building the character of elementary school students contextually and sustainably. Recommendations are given to schools and policy makers to strengthen teacher training and curriculum development that supports this approach.